Cytomegalovirus in liver transplant recipients. Issue 4 (August 2017) - Herman, David; Han, Hyosun
Abstract : Purpose of review: Cytomegalovirus (CMV) is the most common opportunistic infection following solid-organ transplant and remains a cause of life-threatening disease and allograft rejection in liver transplant recipients. The purpose of this review is to highlight the current strategies in diagnosis and management of this disease in this vulnerable population. Recent findings: Identification of high-risk individuals and aggressive treatment with antiviral agents, either via prophylaxis or by early initiation during active disease, has become the standard of care. Despite this, CMV continues to exert a significant effect, remaining a major cause of morbidity and mortality. Summary: Given these findings, continuing efforts are underway to determine whether further therapy, vaccination, or alternative management strategies may improve outcomes in solid-organ transplant recipients. Until that time, however, aggressive monitoring of post-transplant patients for signs and symptoms of CMV infection is the best strategy to prevent solid-organ loss and death.